The Effectiveness of Psychological Empowerment on Emotional Cognitive Regulation and Parenting Self-Efficacy in Female-Headed Households - Nasim Nafar; Mohammad Hossein Fallah; Seyed Mahmood Mirzamani Bafghi (Iranian Journal of Educational Research)
Objective: The aim of this research is to examine the impact of psychological empowerment on emotional cognitive regulation and parenting self-efficacy among female-headed households. Methods: This quasi-experimental study utilized a pretest-posttest design with a control group and quarterly follow-up. Thirty women heading families in Isfahan were randomly assigned to experimental and control groups (15 individuals in each group). The experimental group underwent 10 sessions of psychological empowerment therapy, whereas the control group did not undergo any intervention. Participants completed the Cognitive Emotion Regulation Strategies and Parenting Self-efficacy Questionnaire during pre-test and post-test stages to gather data, which was subsequently analyzed using covariance. Results: The findings indicated that approximately 78% of the variability in emotional regulation scores and 25% of the variability in parental self-efficacy scores were influenced by psychological empowerment. Conclusions: The outcomes of this study lay the groundwork for understanding the impact of psychological empowerment on emotional cognitive regulation and parenting self-efficacy within female-headed families.